Persepsi Mahasiswa UNESA Mengenai Golput Pasca Penayangan Film Sexy Killers - Dwi Ramadhania; Maya Dwi Susanti; Bilqis Sayyidatul; Nina Anggraeni; Agus Machfud Fauzi (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2020)
Screening of sexy killers films ahead of the 2019 elections simultaneously caused propaganda in the community. After the screening of the film, there were abstentions which were quoted on many social media and abstentions have been proven as much as 19.24% of the votes. This then motivates researchers to find out students' perceptions as elements of the academic community assessing abstentions when linked to the screening of sexy killers films. The method used in this research is descriptive qualitative and using interview techniques in information retrieval. The theory used is perception according to Pride and Farrel. The results of this study indicate that the students of Unesa understand the film about the socio-economic impacts felt by the community around the mining area. Besides that the film also explained the other side of the existing paslon figure. Need deep understanding to avoid abstentions. Students are of the view that abstentions can influence the results of the 2019 elections.